Desmoid-type fibromatosis in splenic hilum with rupture of lienal artery aneurism in a 17-year-old male - Krsteska, Blagica; Jovanovikj, Rubens; Darko DJambaz; Ognjenovic, Ljubomir; Eftimov, Aleksandar (My University, 2023)
Desmoid Fibromatosis (DF) is locally aggressive benign fibroblastic or myofibroblastic tumor with no me- tastatic potential, but has high recurrence rate. The symptoms vary according to tumor location, abdominal or extra-abdominal. In this study we present a case of a 17-year-old male with intraabdominal bleeding due to rupture of lienal artery aneurism in splenic hilum where desmoid fibromatosis was found. From abdo- minal cavity 3L free blood was evacuated. Immunohistochemistry revealed nuclear positivity for β-catenin stain favoring the diagnosis of desmoid type fibromatosis. Some of the cells showed SMA positivity, while CD34, S100 and CD117 were negative. Additional molecular analysis from 3 ml peripheral blood was made by NGS showing intergenic variant on position 51549496 with frequency of 46,4% which is highly pathoge- nic. Intraabdominal fibromatosis has very unpredictable outcome when diagnosed incidentally. Molecular analysis should reveal more genetic alterations in publishing these case presentations.
Keywords: Myofibroblastic tumor; Hemoperitoneum; β-catenin mutations